Enhancing Competence and Legal Safeguards for Foreign Medical Professionals under the ASEAN Mutual Recognition Arrangement (MRA): A Case Study of Indonesia - Roswita Sitompul; Tommy Leonard; Kartina Pakpahan; Thela Valentine; Merry Roseline Pasaribu (Khazanah Hukum, 2023)
This study aims to analyze the regulation of the medical profession in Indonesia in implementing the Mutual Recognition Arrangement (MRA), as well as the legal response to violations by foreign doctors and the government's efforts to increase the competitiveness of ASEAN foreign doctors in MRA professional standards. The normative-empirical method is used by collecting data through field studies, literature studies, and qualitative analysis. The results of the study show that a number of regulations including the Medical Practice Act, the Health Law, and the Presidential Decree regarding foreign workers governs the regulation of the medical profession in Indonesia related to MRA. The government is also trying to increase the competitiveness of foreign doctors by providing quality health infrastructure and creating a conducive investment climate. Legal responsibility for foreign doctors' violations of the medical profession includes civil, criminal and administrative aspects. This research provides insight into legal protection for the medical profession in the implementation of MRA and emphasizes the importance of government steps in increasing the competence of foreign doctors to maintain professional standards in the ASEAN context.